Validity and Reliability Study of the Indonesian Empathy Quotient–Systemizing /Quotient for Children (EQ-C/SQ-C) - Yudi Reza Phallapi; Tjhin Wiguna; Eloisa Nathania; Kamila Ratu Chaidir; Kindah Mahdiyyah (International Journal of Child Development and Mental Health, 2018)
Empathy and systemising skill are very important for strengthening pro-social behaviour. However, the EQ-C/SQ-C questionnaire was originally framed in the English language and has not been translated into the Indonesian language. Therefore, this study aims at validating and to analysing the reliability of the EQ-C/ SQ-C in the Indonesian version. The study used a cross-sectional design that included 752 primary school students and their parents .They were selected randomly in accordance with their willingness to participate in the study. The parents were asked to fill the EQ-C/SQ-C questionnaire. The educational background of the parents was at least secondary high school. The analysis included content and construct validity, internal consistency reliability test. All analyses were run on SPSS for Mac version 21. The age of children ranged between 4–14 years, with mean (SD) being 10.07 (0.07). The educational background of parents was mostly above the high school degree. The content validity analysis showed that four statements of the EQ-C/ SQ-C Indonesian version were not validated by the experts’ judgment; therefore, they were deleted. The construct validation done after deleting 7 items of EQ-C and 6 items of SQ-C, the requirement for principle component analysis was accomplished. Principal component analysis of EQ-C/SQ-C items extracted three components with eigenvalue >1. These two components justified 64.39% of the total EQ-C/SQ-C variance. Internal consistency was good with Cronbach’s alpha 0.979. EQ-C/SQ-C Indonesian version had a shorter version with 38 items. It was a valid and reliable questionnaire to measure the empathy and systemizing skills among Indonesian children.